2016
DOI: 10.1007/s10648-016-9388-9
|View full text |Cite
|
Sign up to set email alerts
|

Task Experience as a Boundary Condition for the Negative Effects of Irrelevant Information on Learning

Abstract: Research on multimedia learning has shown that learning is hampered when a multimedia message includes extraneous information that is not relevant for the task, because processing the extraneous information uses up scarce attention and working memory resources. However, eye-tracking research suggests that task experience might be a boundary condition for this negative effect of extraneous information on learning, because people seem to learn to ignore task-irrelevant information over time. We therefore hypothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
31
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 61 publications
6
31
0
1
Order By: Relevance
“…First, to check whether we could replicate prior findings by Rop et al (2016) that performance is initially hampered by mismatching pictures, we performed a mixed ANOVA on recall performance with Word Block (first or second) as within-subjects factor and Picture Match (matching or mismatching) as between-subjects factor. Then, to test our hypothesis concerning the effects of the location change on recall performance we conducted 2 × 2 ANOVAs with Picture Match (matching or mismatching) and Location Change (yes or no) as between-subjects factors on recall performance in Block 3.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…First, to check whether we could replicate prior findings by Rop et al (2016) that performance is initially hampered by mismatching pictures, we performed a mixed ANOVA on recall performance with Word Block (first or second) as within-subjects factor and Picture Match (matching or mismatching) as between-subjects factor. Then, to test our hypothesis concerning the effects of the location change on recall performance we conducted 2 × 2 ANOVAs with Picture Match (matching or mismatching) and Location Change (yes or no) as between-subjects factors on recall performance in Block 3.…”
Section: Resultsmentioning
confidence: 99%
“…Combined, these findings suggest that changing the location of matching pictures seemed to have a small negative effect on word learning. Eye-tracking data from the study by Rop et al (2016) showed that matching pictures continuously attracted a substantial amount of attention, from an average of 76% of fixation time in Block 1 to 60% in Block 3, over the course of the experiment. Thus, in the present study, when the location of these pictures suddenly changed in Block 3, participants might have wondered why the location of the pictures changed, which would distract from learning the definitions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations